A pervasive information approach to urban geography research: the case of Turku - Tedeschi Miriam; Heino Hanna; Resmini Andrea (Taylor & Francis, 2025)
The article explores the Pervasive Information Architecture (PIA) framework as a theory and set of tools that support the identification of both the multiple physical/digital, spatially oriented elements that make up urban life and, importantly, the obstacles and barriers to information flow between them. As an example, the article presents the application of the framework in studying how first-generation immigrants experience the urban natural environment in Turku, Finland. This research contributes to advancing our understanding of how Pervasive Information Architecture can be effectively used to analyse, design, and optimize urban landscapes, thereby promoting a more inclusive urban development.